Styring gjennom nettverk. Koordinering, ansvarliggjøring og institusjonalisering av styringsnettverk i norske byregioner - Holmen, Ann Karin Tennås (Public Policy and Administration, 2011)
In recent years the city region has developed as an arena for policy development. In this arenadifferent interests and values are coordinated in order to solve complex problems. InNorwegian city regions this is especially visible within development policy. In this policyarena, city centers and surrounding municipalities are working together and both public andprivate stakeholders are involved. In this thesis this is referred to as governing throughnetworks, or network governance. The development of governance networks as frame forpolicy development raises principal questions related to whether this is a wanted developmentregarding efficient and democratic governance.Case studies of three city-regional cases from Tromsø, Stavanger, and Bergen are studiedalong three main dimensions; coordination, democratic accountability, andinstitutionalization. The main question under investigation is what significance developmentof a governance network can have for effective and democratic governance. The balance liesin the relation between creating better and more efficient collaborative solutions and at thesame time securing acceptance and legitimacy based on democratic norms. Such an approachprovides important arguments related to the future role of governance networks as acoordination mechanism, a tool for governance, and as a policy arena.The main goal with this dissertation is to develop a better understanding of how governancenetworks are organized and how this affects network processes and the overall influence inNorwegian city regional development policy. Three research questions are posed anddiscussed through three articles. Through these articles a basis for a comprehensive analysis islaid. The first article focuses on coordination of different interests and how this is played outwithin the frames of governance networks. The article points at the significant role of theoperative manager working in between interests by creating room for balancing efficient anddemocratic performance. Adaptation and structural ...